Qualitative assessment of pica experienced by frequent blood donors - Chansky, Melanie C.; King, Melissa R.; Bialkowski, Walter; Bryant, Barbara J.; Kiss, Joseph E.; D'Andrea, Pam; Cable, Ritchard G.; Spencer, Bryan R.; Mast, Alan E. (Transfusion (Philadelphia, Pa.), 2017)
BACKGROUND Pica, the compulsive consumption of ice or other nonnutritious substances, is associated with iron deficiency, a common negative consequence of frequent blood donation. Because of this, blood donors, such as those participating in the Strategies to Reduce Iron Deficiency (STRIDE) study, are an ideal population to explore pica and iron deficiency. STUDY DESIGN AND METHODS STRIDE was a 2‐year intervention trial to assess the effectiveness of iron supplementation for mitigating iron deficiency in frequent blood donors. Subjects completed baseline and follow‐up questionnaires that included questions about pica symptoms. In‐depth telephone interviews were conducted with 14 of these subjects reporting pica symptoms and eight presumed controls (casual ice chewers) to gain a deeper understanding of pica symptoms and their impact on daily life and to make a final determination on the presence of pica. RESULTS Pica was confirmed in five of the 14 subjects reporting symptoms and in two of eight controls. Outcome misclassification based on the questionnaire was attributed to inadequate assessment of several pica symptoms identified during the interview. Comparison of subjects' repeated quantitative iron measurements taken throughout STRIDE with subjects' final adjudicated pica status revealed a positive relationship between development of pica and worsening iron status; the opposite was found in those whose pica symptoms resolved. CONCLUSION Continued refinement of pica symptom questions will allow for rapid and accurate detection of pica in frequent blood donors and confirmation of successful treatment with iron supplements.